PENGARUH STRUKTUR MODAL DAN INVESTASI TERHADAP NILAI PERUSAHAAN PADA SUB SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Augustin, Jeneva; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine the effect of Capital Structure, Investment on Corporate Value in Pharmaceutical Companies Listed on Indonesian Stock Exchange (IDX). The ratio used to measure capital structure as independent variable is Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), Longterm Debt to Assets Ratio (LDAR), and Longterm Debt to Equity Ratio (LDER). The ratio used to measure investment is Price Earning Rasio (PER). Meanwhile, the ratio used to measure Company Value is Price Book Value (PBV). The method used to observe the effect of capital structure, investment on corporate value is by using simple linear regression and multiple linear regression. Data used in this research are secondary data, financial report and annual report annual report. The data listed on the Indonesian Stock Exchange (IDX) for 5 years from 2011 to 2015. Sampling is done by purposive sampling, which is used is 7 companies. Data analysis using simple linear regression analysis, multiple linear analysis, t test, f test and coefficient of determination test. Data analysis using multiple linear regression analysis with SPSS 21. The result of the analysis shows that capital structure variable only Debt to Assets ratio (DAR) which affects the value of pharmaceutical companies of research sample that listed in Indonesia Stock Exchange, and investmens variable does not affect the value of pahrmaceutical companies of research sample that listed in Indonesia Stock Exchange. The result of simultaneous research shows there is influence from capital stucture variable, investments on the value of Pharmaceutical company of research sample listed in Indonesian Stock Exchange (IDX). Keywords : capital structure, investment, corporate value